2017
DOI: 10.33312/ijar.384
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Individual Characteristics, CSR Information, Financial and Non-Financial Compensation to Job Seekers Interests in A Company

Abstract: Human resources are the key to achieving and maintaining corporate goal(s). Obtaining high-quality human resources is a challenging task for every corporation. Therefore, corporations compete in providing attractive compensation packages to both its current and prospective employees. The objective of this study is three folds. Firstly, this study seeks to explore the effect of information on compensation and corporate social responsibility (CSR) disclosures toward fresh-graduate job seekers interests of a comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…26, No.3, 2023 become increasingly important in Indonesia's developing economy, which several studies have highlighted. Agritansia et al (2017) revealed that CSR is essential for recent college grades. The research indicates that CSR disclosure is an important tool for organizations to use in their hunt for top-tier employees.…”
Section: Literature Reviewmentioning
confidence: 99%
“…26, No.3, 2023 become increasingly important in Indonesia's developing economy, which several studies have highlighted. Agritansia et al (2017) revealed that CSR is essential for recent college grades. The research indicates that CSR disclosure is an important tool for organizations to use in their hunt for top-tier employees.…”
Section: Literature Reviewmentioning
confidence: 99%